Translational research of antidepressants with an example of cannabidiol effects - Alexandra Šulcová (Archives of Depression and Anxiety - Peertechz Publications, 2020)
Despite that not all symptoms of depression can be achieved in animals the translational animal models can mimic the aspects of human depressive disorders in terms of disease symptoms as well as their neurobiological mechanisms. Results of testing the antidepressant drug effects in behavioral animal models of depression are presented. In these models, depressive-like behavior is induced by various stress factors in laboratory animals. However, patients suffering from the Therapeutic Resistant Depression (TRD) do not have high-stress markers. Thus, animals with predisposing factors leading to heightened stress responsiveness as a tool for discovering drugs for human TRD treatment are also presented. Antidepressant treatment effects are reported to be achieved through complex influences on body responses associated to reward, stress, and inflammation, the processes reported to be influenced by activities of the Endocannabinoid System. Cannabidol (the cannabinoid without abuse potential) is reported as an antidepressant agent.